RAPD analysis of callus regenerated and seed grown plants of maize (Zea mays L.). - VASCONCELOS, M. J. V. de (2008)
Genetic and cytogenetic changes are frequently observed in plants regenerated from tissue culture. This phenomenon, termed somaclonal variation, is undesirable in genetic transformation processes. DNA-based molecular markers have been used to characterize and evaluate genetic variability among individuals. The RAPD technique was used to evaluate somaclonal variation in maize plants derived from tissue culture from the maize inbred line L48 (derived from Suwan). Forty seven different decamer oligonucleotide primers generated 221 amplification products, 130 of them being polymorphic. Genetic divergence was calculated by the Nei´s distance based on the presence (1) or absence (0) of DNA bands in the different analyzed samples. Cluster analyses divided the samples into three distinct groups, considering an upper limit of 0.38 genetic distances. The first group included the tissue culture-derived calli, the second one the regenerated plants, and the seed-derived plants formed the last group. The results indicated that segregation was still present in the inbred line L48 after six cycles of selfing and/or that different clones of the same age accumulated different types of genetic modifications (0.05 of genetic distance). These modifications seem to be directly correlated with the potential for callus regeneration. As the age of the callus increased from 13 to 25 months, regeneration decreased about 28 times. These results indicate that RAPD technique can be used as a potent and easy-to-use tool to identify maize inbred lines less susceptible to somaclonal variation when cultured in vitro, a fundamental step in plant genetic transformation. Variações em genética e citogenética são frequentemente observadas em plantas regeneradas em cultura de tecidos. Esse fenômeno, chamado variação somaclonal, é indesejável nos processos de transformação genética. Marcadores moleculares baseados em DNA têm sido amplamente usados para caracterizar e avaliar variabilidade genética entre indivíduos. Foi usada a técnica de RAPD para avaliar a variação somaclonal em plantas de milho derivadas de cultura de tecidos e sementes da linhagem L48 (derivada de Suwan). Quarenta e sete diferentes oligonucleotídeos decâmeros geraram 221 produtos de amplificação, 130 polimórficos. Divergência genética foi calculada usando distância de Nei, baseada na presença (1) e ausência (0) de produtos de amplificação de DNA. Análises de clusters dividiram as amostras em três grupos distintos, considerando o limite superior de 38% de distancia relativa. O primeiro grupo, incluiu os calos derivados de cultura de tecido, o segundo, as plantas regeneradas e o terceiro e ultimo, as plantas derivadas de semente. Os resultados indicaram que a linhagem L48 após seis ciclos de autofecundação e/ou de diferentes clones da mesma idade, acumulou diferentes tipos de variação genética. Com o aumento da idade dos calos de 13 para 25 meses, a regeneração diminuiu cerca de 28 vezes. Esses resultados indicaram que a técnica de RAPD pode ser usada como uma potencial e fácil ferramenta para identificar linhagens menos susceptível à variação somaclonal, quando cultivada in vitro, fundamental etapa para transformação genética.